A 24-hour perioperative case study on argatroban use for left ventricle assist device insertion during cardiopulmonary bypass and veno-arterial extracorporeal membrane oxygenation. (May 2019) - Fernandes, Philip; O'Neil, Michael; Del Valle, Samantha; Cave, Anita; Nagpal, Dave
A 44-year-old male with ongoing chest pain and left ventricular ejection fraction <20% was transferred from a peripheral hospital with intra-aortic balloon pump placement following a non-ST-elevation myocardial infarction (STEMI). The patient underwent emergent multi-vessel coronary artery bypass grafting requiring veno-arterial (VA) extracorporeal membrane oxygenation (ECMO) on post-operative day (POD)#9 secondary to cardiogenic shock with biventricular failure. Due to clot formation, an oxygenator change-out was necessary shortly after initiation. Following a positive heparin-induced thrombocytopenia (HIT) assay, a total circuit exchange was required to eliminate all heparin coating and argatroban was deemed the anticoagulant of choice due to acute kidney injury. On POD#24, the decision was made to implant a left ventricle assist device (LVAD) as a bridge to heart transplantation. There was difficulty achieving an activated clotting time (ACT) >400 s: multiple argatroban bolus doses were required, along with accelerated up-titration of infusion dosing. Despite maintaining an ACT >484 s, clot formation was observed in the cardiotomy reservoir prior to separation. Subsequently, the patient developed severe disseminated intravascular coagulopathy, with both intra-cardiac and intravascular thrombi, requiring massive transfusion and continuous cell saving due to severe hemorrhage post cardiopulmonary bypass (CPB). The patient received a total of 105 units of plasma, 74 units of packed red cells, 19 units of platelets, 13 bottles of 5% albumin, 6 units of cryoprecipitate and 2 doses of factor VIIa intraoperatively over the course of 24 hours. A total of 19.7 L of washed red blood cells were returned to the patient from the cell saver. With the LVAD in place, the patient developed transfusion-related acute lung injury and acute respiratory distress syndrome with right ventricular dysfunction requiring VA ECMO once again. On POD#30, ECMO was discontinued and the patient was discharged from the intensive care unit (ICU) on POD 66. After a very complex post-operative stay with numerous surgeries and extensive rehabilitation, the patient was discharged home with the LVAD on POD#112.